Reflexive eye saccadic parameters in Parkinson’s disease - Pah, Nemuel D.; Ngo, Quoc C.; McConnell, Nicole; Polus, Barbara; Kempster, Peter; Bhattacharya, Arup; Raghav, Sanjay; Kumar, Dinesh K. (Frontiers in Medical Technology, 2024)
Introduction: Abnormal reactive saccade, with reduced saccadic gain, impaired smooth pursuit, and unwarranted reactions are clinically used to assess people with Parkinson's disease (PwPD).However, there are inconsistent findings related to other saccade parameters such as latency and transition times. This study aimed to identify differences in the reflexive saccade parameters of early stage PwPD and aged-matched control (AMC). Methods: In this observational study, the reactive eye-gaze was recorded for 70 participants (42 PwPD) and parameters of reflexive saccades and eye-gaze fluctuations were extracted. These parameters were then statistically analyzed using the Mann-Whitney U-test. Results: Results showed that PwPD had significantly shorter latency than AMC for reflexive saccadic movement away from the center of the screen.The overshoot as a fraction of the screen width, a measure of the inaccuracy in reaching the target, was also significantly higher for PwPD. PwPD had greater horizontal and vertical eye gaze fluctuation with a steady target. The numbers of invalid saccades, i.e. when the gaze goes in the opposite direction from the target movement or is considered anticipatory, were similar for both groups; PwPD with 33.43% and AMC with 25.71%. Discussion: This study shows that there are significant differences in the reflexive saccade of PwPD and AMC measured using an inexpensive eye-tracking device. The presence of invalid saccade trials, and differences between towards and away from screen center, both of which were not considered in earlier studies, may explain the discrepancies between earlier studies. The outcome of this study has the potential to be made a device that would assist neurologists in the assessment of PwPD.